“And So We Write”: Reflective Practice in Ethnotheatre and Devised Theatre Projects (LEARNing Landscapes, 2022)
This paper follows the author’s trajectory as he collaboratively experimented with ethnodrama (theatre scripts generated from interviews, media artifacts, and written media) and devised theatre performance (theatre collaboratively created with a group), culminating in the analysis of a performance with high school students combining elements of these forms. The author defines the forms, illuminates how he engaged with them over time, and how he adapted elements of them for work with his high school students. The author proposes a framework deduced from these experiences as a provocation for future performance projects and as a demonstration of an educator’s reflective practice.
Keywords: devised theatre; ethnodrama; devised theater; youth theatre; youth theater; reflective practice; reflexive practice